Mortality-Indexed Annuities. Managing Longevity Risk via Product Design - Andreas Richter; Frederik Weber (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2009)
Longevity risk has become a major challenge for governments, individuals, and annuity providers in most countries, and especially its aggregate form, i.e. the risk of unsystematic changes to general mortality patterns, bears a large potential for accumulative losses for insurers. As obvious risk management tools such as (re)insurance or hedging are less suited to manage an annuity provider's exposure to aggregate longevity risk, the current paper proposes a new type of life annuities with benefits contingent on actual mortality experience, and it also details actuarial aspects of implementation. Similar adaptations to conventional product design exist in investment-linked annuities, and a role model for long-term contracts contingent on actual cost experience is found in German private health insurance so that the idea is not novel in general, but it is in the context of longevity risk. By not or re-transferring the systematic longevity risk insurers may avoid accumulative losses so that the primary focus in an extensive Monte-Carlo simulation is on the question of whether and to what extent such products are also advantageous for policyholders in contrast to a comparable conventional annuity product.
urn:nbn:de:bvb:19-epub-10994-4
Keywords: G22; G23; C15; 650; Longevity risk; systematic risk; risk avoidance; mortality-indexed annuities; Sterblichkeit; Indexberechnung; Monte-Carlo-Methode; Wirtschaftsmathematik; Risikomodell; Risikomanagement; Versicherungsmathematik